The CMV-encoded G protein-coupled receptors M33 and US28 play pleiotropic roles in immune evasion and alter host T cell responses - White, Timothy M.; Bonavita, Cassandra M.; Stanfield, Brent A.; Farrell, Helen E.; Davis-Poynter, Nicholas J.; Cardin, Rhonda D. (Frontiers in Immunology, 2022)
Human cytomegalovirus (HCMV) is a global health threat due to its ubiquity and lifelong persistence in infected people. During latency, host CD8+ T cell responses to HCMV continue to increase in a phenomenon known as memory inflation. We used murine CMV (MCMV) as a model for HCMV to characterize the memory inflation response to wild-type MCMV (KP) and a latency-defective mutant (M33stop), which lacks M33, an MCMV chemokine receptor homolog. M33 is essential for normal reactivation from latency and this was leveraged to determine whether reactivation in vivo contributes to T cell memory inflation. We found that M33stop triggers memory inflation specific for peptides derived from the immediate-early protein IE1 but not the early protein m164, in contrast to wild-type MCMV. During ex vivo reactivation, gene expression in M33stop-infected lung tissues was delayed compared to wild-type virus. Normal gene expression was partially rescued by substitution of the HCMV US28 open reading frame in place of the M33 gene. In vivo depletion of T cells in immunoglobulin heavy chain-knockout mice resulted in reactivation of wild-type MCMV, but not M33stop, confirming the role of M33 during reactivation from latency. Further, we found that M33 induces isotype-specific downregulation of MHC class I on the cell surface and inhibits cellular apoptosis, suggesting previously unappreciated roles in immune evasion.